Distribution and antibacterial susceptibility pattern of isolated bacteria from endotracheal aspirates among ventilator-assisted pneumonia patients in Indonesia - Andayani, Novita; Mahdani, Wilda; Nisyra, Mailani; Agustin, Heidy (Narra J, 2023)
An accurate and timely identification of causative microorganisms as well as determination of their antibiotic susceptibility patterns will help in the selection of proper antibiotics and prevention of their misuse in pneumonia patients. The aim of this study was to determine the distribution and antibiotic susceptibility pattern of bacteria isolated from endotracheal aspirates of ventilator-assisted pneumonia patients in Indonesia. A retrospective cross-sectional study was conducted at Dr. Zainoel Abidin Hospital, a provincial reference hospital in Banda Aceh, Indonesia, from January to December 2021. Ventilator-assisted pneumonia patients aged ≥17 years treated in the hospital were considered eligible. Antibiotic susceptibility was valuated using Kirby-Bauer disc-diffusion followed with VITEK 2 Compact. We included 57 patients of which 73.7% males and 26.3% aged 56–65 years (represent the majority group of the patients). Each patient reported at least one comorbidity and the average duration of receiving mechanical ventilation was 8.68 days, and more than half (59.7%) of the patients had a poor clinical outcome (died). A total 57 bacteria isolates (consisting nine species) were recovered; 68.5% Gram-negative and 31.5% Gram-positive bacteria. Among 57 patients, Acinetobacter baumannii was the most frequent isolated Gram-negative bacteria (19.3%), followed by Klebsiella pneumoniae (17.5%), Pseudomonas aeruginosa (15.8%), and Achromobacter denitrificans (12.3%). A. baumannii exhibited <70% sensitivity to aminoglycoside and carbapenem antibiotics and 100% resistance to third-generation cephalosporins. The most abundant Gram-positive bacteria was Staphylococcus aureus (17.5%), followed by S. haemolyticus (10.5%) and S. epidermidis (3.5%). All S. aureus were sensitive to linezolid, tigecycline, vancomycin, and macrolide antibiotics (azithromycin, clarithromycin, clindamycin, and erythromycin), whereas 50% were sensitive to some beta-lactams. However, 50% of S. aureus were methicillin resistant S. aureus (MRSA). Given the magnitude of multi-drug resistance, an empiric antimicrobial therapy in particular to specific settings and implementation of antibiotic stewardship programs are crucial.